Pattern of Mefloquine Ingestions Reported to Texas Poison Centers. (April 2016) - Forrester, Mathias B.
Background. Mefloquine is an antimalarial drug available in the United States that in 2013 was given a black box warning about the potential for neurologic and psychiatric adverse effects.Objective. This study describes mefloquine ingestions reported to a large statewide poison center system.Methods. The distribution of all mefloquine ingestions reported to Texas poison centers during 2010 to 2014 was determined for dose, year, patient age and gender, exposure site, ingestion reason, management site, medical outcome, clinical effects, and treatments.Results. Of 63 total cases, the mean dose was 672 mg (range = 188-3500 mg). The patient age distribution was 5 years or less (27.0%), 6 to 19 years (12.7%), and 20 years or more (58.7%); 52.4% of the patients were male. Therapeutic errors accounted for 71.4% of the cases and adverse reactions 19.0%. The management site was 52.4% on site, 19.0% already at/en route to a health care facility, and 23.8% referred to a health care facility. The medical outcome was not serious in 79.4% of the cases. The most common adverse effects were gastrointestinal (28.6%) or neurological (20.6%) in nature. One case each was reported to have depression, paranoia, and almost psychotic presentation.Conclusions. Few mefloquine ingestions were reported to Texas poison centers. Those that were reported tended to involve adult males and were due to therapeutic error or adverse reaction. Although mefloquine ingestions may result in potentially serious side effects, the exposures reported to Texas poison centers tended not to be serious with few adverse effects and were managed outside of health care facilities.